2023
DOI: 10.1108/tlo-04-2023-0053
|View full text |Cite
|
Sign up to set email alerts
|

Links connecting organizational socialization, affective commitment and innovative work behavior

Nuri Gökhan Torlak,
Taylan Budur,
Noor Us Sabbah Khan

Abstract: Purpose This study aims to investigate the relationships between affective commitment (AC), innovative work behavior (IWB) and organizational socialization strategies (training, coworker support, understanding and future prospects) to ensure the viability and prosperity of businesses in Iraq. Design/methodology/approach The methodology includes demographic analysis, confirmatory factor analysis and structural equation modeling. Findings An analysis of survey data based on a random sample of participating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 114 publications
(199 reference statements)
0
6
0
Order By: Relevance
“…In this sense, providing future prospects is one of the roles of a transformational leader rather than a transactional leader. The results of Torlak et al (2024) also indicated that affective commitment stimulated by future prospects leads to employees' innovative behavior. Then, this innovative behavior will become a driver of organizational change.…”
Section: Do Not Be Afraid Of Failure: Iterate Microlevel Trial and Errormentioning
confidence: 89%
See 4 more Smart Citations
“…In this sense, providing future prospects is one of the roles of a transformational leader rather than a transactional leader. The results of Torlak et al (2024) also indicated that affective commitment stimulated by future prospects leads to employees' innovative behavior. Then, this innovative behavior will become a driver of organizational change.…”
Section: Do Not Be Afraid Of Failure: Iterate Microlevel Trial and Errormentioning
confidence: 89%
“…OST facilitates newcomers' adaptation to their jobs, workgroups, work environment, corporate culture and acceptable behavior in a company (Torlak et al, 2024). Torlak et al (2024) examined the impact of OST on the employees' innovative behavior through improving their commitment. In particular, they focused on affective commitmentpositive emotional attachment to the organization (Torlak et al, 2024) among the elements of organizational commitment.…”
Section: Do Not Be Afraid Of Failure: Iterate Microlevel Trial and Errormentioning
confidence: 99%
See 3 more Smart Citations